Alteration in gut microbiota after colonoscopy: proposed mechanisms and the role of probiotic interventions - Hyeong Ho Jo; Moon Young Lee; Se Eun Ha; Dong Han Yeom; Yong Sung Kim (Clinical Endoscopy)
Colonoscopy, a widely used procedure for diagnosing and treating colonic diseases, induces transient gastrointestinal symptoms and alterations in the gut microbiota. This review comprehensively examines the evidence on alterations in the gut microbiota following colonoscopy and their possible mechanisms. Factors such as rapid colonic evacuation, increased osmolality, and mucus thinning caused by bowel preparation and exposure to oxygen during the procedure contribute to these alterations. Typically, the alterations revert to the baseline within a short time. However, their long-term implications remain unclear, necessitating further investigation. Split-dose bowel preparation and CO2 insufflation during the procedure result in fewer alterations in the gut microbiota. Probiotic administration immediately after colonoscopy shows promise in reducing alterations and gastrointestinal symptoms. However, the widespread use of probiotics remains controversial due to the transient nature of both the symptoms and gut microbial alterations following a colonoscopy. Probiotics may offer greater benefits to individuals with preexisting gastrointestinal symptoms. Thus, probiotic administration may be a viable option for selected patients.